BOOK REVIEW OF DAVID LEVITHAN’S EVERY DAY - Budiyanti, Revina (LANTERN (Journal on English Language, Culture and Literature), 2017)
The purpose of composing this book review is to present to the readers the summary of Every Day novel as well as the review about its strengths and weakness. The reason of choosing this novel is the unique story that this novel offers. This novel tells us about a sixteen year old genderless spirit named A who wakes up in a different body and lives different life every day.As different life means different story, it is interesting to look at how the characters in the novel are going down that road and overcoming every obstacle in almost every chapter.